Community structural characteristics and the adoption of fluoridation. - Smith, R A (1981)
A study of community structural characteristics associated with fluoridation outcomes was conducted in 47 communities. A three-part outcome distinction was utilized: communities never having publicly considered the fluoridation issue, those rejecting it, and those accepting it. The independent variables reflect the complexity of the community social and economic structure, social integration, and the centralization of authority. Results of mean comparisons show statistically significant differences between the three outcome types on the independent variables. A series of discriminant analyses provides furtheor evidence of how the independent variables are associated with each outcome type. Non-considering communities are shown to be low in complexity, and high in social integration and the centralization of governmental authority. Rejecters are shown to be high in complexity, but low in social integration and centralized authority. Adopters are relatively high on all three sets of variables. Theretical reasoning is provided to support the hypothesis and why these results are expected. The utility of these results and structural explanations in general are discussed, especially for public/environmental health planning and political activities.